Cognitive Versus Reinforcement Views of Intrinsic Motivation - Pate, Larry E. (Academy of Management Review, 1978)
The research of Deci and associates regarding the effects of extrinsic rewards on intrinsic motivation has stimulated controversy among cognitive and reinforcement theorists. Theoretical roots of cognitive and reinforcement theories are traced, and the controversy over Deci's research is examined, particularly with regard to Scott's recent critique. Implications of these discrepant positions and potential areas of research and application in work organizations are discussed.